Português para fins específicos e seu ensino no curso técnico de contabilidade - Santos, Vilmária Gil dos (2013)
The focus of this dissertation research focuses on the difficulty of most students, both in the process of reading and writing process, especially in relation to language teaching applied courses. The question we seek to answer points to a way to "teach" Portuguese for young people looking after high school, a specific technical area- in this case, the field of Accounting. As forfield research, we established a Needs Analysis, which guides the instrument for a drawing course able to answer there search question. Listed as objectives to identify, through this analysis, primarily students' difficulties, in particular those relating to the skills of reading and text production, working with genres present in the world of specialty focus, identify reading strategies and production of texts that facilitate students; develop proposed approach in teaching for specific purposes which contemplates production and reading of texts in accounting. The methodology was qualitative assumed, whose foundation is given a dimension of research and action. As a theoretical basis, we use studies: reading from Solé (1998) and Kleiman (2004), text production, derivatives Sautchuk (2003) and Passarelli (2004); approach for specific purposes, assumptions by Celani (2009), Cintra and Passarelli (2008) and Ramos (2009), gender, conducted by Bhatia (1993) and Bazerman (2005); Textual Linguistics, signed in Koch (2001,2009) and Marcuschi (2008). Through out production, the data guided the planning of lessons and evidence that the Needs Analysis is an essential part for an education suited to the needs of the group being studied in courses for specific purposes